Karakteristik Endapan Tras Nagreg untuk Menudukung Pemberdayaan Perekonomian Masyarakat Lokal, Desa Nagreg Kendan, Kecamatan Nagreg, Kabupaten Bandung - Sri Widayati; Dudi nasrudin usman; Sriyanti Sriyanti; Linda Pulungan; Dono Guntoro (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2017)
Characteristics of sediment Tras Nagreg as part of the volcanic process in the region provides anopportunity and potential to be utilized through mining activities. Mining activities, as a capitalintensive,labor-intensive and risk-filled industry, do not always have a negative impact on thesurrounding community, there is something to do with the economic aspects in which all types ofmineral deposits have economic value including tras. Nagreg Kendan Village, Nagreg Subdistrict aspart of Bandung Regency which has tras sediment potential, where in quality and quantity, trassediment in the area has big enough potency to be utilized especially to improve prosperity of localcommunity. Currently, the number of people with productive age is quite a lot, which becomes thecapital for the management of tras going forward, another thing to consider is the existence of thelocation not far from the access road that connects Bandung - Garut, Bandung - Cianjur and Bandung- Jakarta.